The Influence Of Community Participation And The Implementation Of Standard Unit Price Settings On The Quality Of Village Financial Reports In Moutong District - Mulyawan , Mulyawan; Blongkod , Harun; Taruh , Victorson (Jurnal Economic Resource, 2024)
Research Aims: This study aims to determine the effect of community participation and the application of standard unit pricing on the quality of village financial reports in the Moutong District, both partially and simultaneously. Design/methodology/approach: This research uses a quantitative method with a descriptive quantitative approach. The primary data was collected through questionnaires distributed to village officials in the Moutong District. The study involved a sample size of 100 respondents, and the data was analyzed using multiple linear regression analysis. Research Findings: The results show that (1) community participation has a positive and significant effect on the quality of financial reports, (2) the application of standard unit pricing has a positive and significant effect on the quality of financial reports, and (3) simultaneously, community participation and the application of standard unit pricing significantly affect the quality of financial reports. The determination coefficient is 43.1%, indicating that 43.1% of the variability in the quality of financial reports can be explained by community participation and the application of standard unit pricing. Theoretical Contribution/Originality: This study contributes to the understanding of how community engagement and adherence to pricing standards impact the quality of financial reporting in village administrations, providing insights for improved governance and accountability in rural financial management (Book Antiqua 10pt). Research limitation and implication: The study is limited to village administrations in the Moutong District, and the findings may not be generalizable to other regions. Future research could explore additional factors influencing financial report quality or expand the geographic scope of the study. The results have implications for policymakers in enhancing community involvement and standard compliance to improve financial reporting practices.